Perencanaan Mengajar dalam Implementasi Kurikulum - Irwanto (STAI Serdang Lubuk Pakam, 2019)
So that learning and teaching activities can run and be carried out properly and smoothly, teaching planning is needed. Descriptive teaching is defined as the process of delivering information or knowledge from the teacher to students. For the teaching process, the process of conveying knowledge will be more appropriate if interpreted by instilling knowledge. The curriculum as an education program that has been planned systematically, has a very important role in the education of students. Implementation of the curriculum is a process of applying concepts, ideas, programs, or curriculum arrangements into learning practices or new activities so that changes occur in a group of people expected to change. The implementation of the curriculum can also be interpreted as the actualization of the written curriculum in the form of learning. Education unit level curriculum is an operational curriculum that is structured and implemented by each education unit. In the outline of SBC includes five main activities, namely the implementation of the learning process, assessment of learning outcomes, and supervision of the learning process.